DMBT1 promotes basal and meconium-induced nitric oxide production in human lung epithelial cells in vitro - Müller, Hanna; Weiß, Christel; Renner, Marcus; Felderhoff-Müser, Ursula; Mollenhauer, Jan (Histochemistry and cell biology, 2017)
Meconium aspiration syndrome (MAS) is characterized by surfactant inactivation and inflammation. As lung epithelial cells up-regulate nitric oxide (NO) in response to inflammation, the NO production following meconium exposition was examined in relation to expression of Deleted in Malignant Brain Tumors 1 (DMBT1), a protein with functions in innate immunity and inflammatory regulation. Here, DMBT1 expression was analyzed by immunohistochemistry in postmortem lung sections from patients with MAS. The lung epithelial cell line A549, stably transfected with a DMBT1 (DMBT1+ cells) expression plasmid or with an empty expression plasmid (DMBT1− cells), was exposed to meconium. NO was determined in dependence of aminoguanidine (inducible NO synthase inhibitor), steroids and lipopolysaccharide (LPS). DMBT1 is highly expressed in lungs with MAS. In the absence of meconium, DMBT1+ cells showed a higher NO production than the DMBT1− cells (p = 0.0090). Meconium led in DMBT1− and DMBT1+ cells to elevated NO levels (p < 0.0001), but with a higher NO level in DMBT1+ cells (p < 0.0001). Aminoguanidine, an iNOS inhibitor, reduced the higher NO production in DMBT1+ cells (p = 0.0476), but NO levels remained above NO production from DMBT1− cells (p = 0.0289). Dexamethasone diminished NO production in DMBT1+ cells after meconium exposition (p = 0.0076). Combined addition of LPS and meconium significantly increased NO production in both cell types (p < 0.0001). In comparison to exposure with only meconium, the combined addition of LPS and meconium to the cells increased NO levels in both DMBT1− cells (p = 0.0030) and DMBT1+ cells (p = 0.0028). In conclusion, basal and meconium-induced NO production in lung epithelial cells is positively regulated by DMBT1.